Strategic analysis of Akademi Binaan Malaysia (Sarawak) Sdn. Bhd. / Wan Ahmadi Wan Zaine ... [et al.] - Wan Zaine, Wan Ahmadi; Sahat, Azeni; Manggoi, Romeo Sanggat; Saba, Siniter; Yunus, Mohd Shah (2004)
This Applied Business Project (ABP) is a partial fulfillment of Executive Masters in Business Administration (EMBA) program. Students were required to undertake and produce an Applied Business Project in the form of a consultation work's report as a final assignmént. This study must apply theories and principles that have been learnt throughout the EMBA program to solve specific problems faced by business firms that have consent their organization to be studied.